Hubungan Pengetahuan, Sikap dengan Dukungan Keluarga sebagai Pengawas Kepatuhan Minum Obat Penderita Tuberkulosis Paru - Nour Sriyanah; Suradi Efendi; Halmina Ilyas; Nadira Nadira (PT.Mantaya Idea Batara, 2022)
Tuberculosis (TB) is an infectious infectious disease caused by the bacterium mycobacterium tuberculosis that attacks various organs, especially the lungs. Family support greatly supports the successful treatment of Pulmonary TB patients by reminding patients to take medication. Meanwhile, the family support provided is closely related to the knowledge and attitudes possessed. The purpose of this study is to find out the relationship between knowledge and attitudes with family support as supervisors of taking drugs in patients with pulmonary tuberculosis in the Bontoa Health Center Working Area, Maros Regency. This type of research is analytical research with a cross-sectional study approach. The population in this study was the families of patients as supervisors of taking drugs as many as 44 people and the sample who became drug supervisors (PMO) amounted to 35 people using accidental sampling techniques with questionnaire sheet instruments to take respondent data. The results showed that 20 respondents (57.1%) had knowledge in the good category and 19 respondents (54.3%) had a positive attitude, and there was a relationship between knowledge (p = 0.021) and attitude (p = 0.009) with the support of families as supervisors of taking drugs in patients with pulmonary tuberculosis in the Bontoa Health Center Work Area, Maros Regency. The conclusion in this study is that there is a relationship between knowledge and attitudes with family support as supervisors of taking drugs in pulmonary tuberculosis sufferers in the work area of the bontoa health center in Maros district, and advice to the government through relevant health officials to improve the knowledge and attitudes of drug-taking supervisors (PMO) in their area in order to increase support for family members suffering from pulmonary TB, so that it can increase the cure rate of sufferers. .